IMPLEMENTASI KEBIJAKAN PENETAPAN PAJAK KENDARAAN BERMOTOR PADA KANTOR BERSAMA SAMSAT AMURANG MINAHASA SELATAN - SOPUTAN, INDRIANI; LONDA, VERY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
This study aims to explain the implementation of the motor vehicle tax determination policy at thesamsat amurang minahasa selatan joint office. This research uses qualitative research, and datacollection techniques are carried out by means of literature, observation, interviews and documentation.The theory of the approach used is based on 4 indicators as follows (i) communication, (ii) resources, (iii)the attitude of the executor, (iv) the bureaucratic structure of the organization. The results of this studyindicate that the implementation of the motor vehicle tax determination policy at the samsat amurangminahasa selatan joint office is carried out well in terms of communication, resources, executive attitudes,bureaucratic structure and organization. To further improve the principle of implementing the motorvehicle tax determination policy at the south minahasa samsat amurang joint office, it is hoped that theofficers will improve their performance again in order to achieve an effective and efficient performancetowards services.Keywords : implementation, policy, determination, tax, vehicle, motor.